The Effect of Moderate Organizational Collectivism on Entrepreneurship Orientation and Interactions on SME Innovation Performance - Effendi, Mohammad Irhas; Sukarno, Agus; Nusanto, Gunawan; Amallia, Bunga Alfausta; Adisti, Trisna (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to examine the relationship between Entrepreneurial Orientation (EO) and Interaction Orientation (IO) market approaches in developing countries. This study uses two market methods using a survey approach. This study collects data from 110 SMEs in Yogyakarta and analyzes it using PLS. Research findings indicate that EO and IO have a beneficial impact on innovation performance. The impact of EO and IO on business innovation performance was not found to be moderating in this study. Research findings support strategic planning by recommending that managers focus on two market approaches to increase innovation success.